Using GPS technology and GIS distance measurement analysis to examine the physical features of road access and trails in SISFEC - Amran, Mohamad Afiq (2016)
Forest road has been used in many kinds of forest classification and each forest road has their function and purposes based on forest class have been set. SISFEC is one of the research and education forest classified in Permanent Forest Reserve (PRF) that give benefits to the local community, especially in Puchong area. SISFEC provides a lot of interesting places used for education and recreation activities which can be accessed by using existing forest roads and trails. In this study, physical features of existing forest road access and trails in SISFEC was spatially located and examined using GPS technology and GIS Distance Measurement Analysis. Through this study, there are 75 stations was categorised as damaged road and most of damaged road was caused by gully with 36 stations was recorded. Distance Measurement Analysis was used to propose and measure the distance of most interesting places for existing forest roads or trails. This analysis helps to determine the best road access with shortest distance to the nearest selected features, giving more options for better decision making. However, constrains like slope and river have been used as cost surface prior to Distance Measurement Analysis conducted. The final output of this analysis is map with details of new proposed trails in SISFEC. The results of the study showed that the nearest distance from existing forest road and trails to the nursery site with the distance of 20.124m and the longest distance from the existing forest road to Permatang Kuang with the distance of 1097.379m. Based on the result, the new proposed trails give better road accessibility by considering slope evaluation and terrain topography compare to the existing road with the shortest distance. Hence, it is useful for decision making for planning forest road access.